Предмет: Математика,
автор: Аноним
розкласти на множники - 4y²+11y+3
Ответы
Автор ответа:
0
-4y²+11y+3
Представим 11y в виде 12y-y
Получим: -4y²+12y-y+3
-4y²+12y-y+3= -4y*(y-3)-(y-3)= -(y-3)*(4y+1)
---------------------------------------------------
-4y² + 11y + 3
Уявімо 11y у вигляді 12y-y
Отримаємо: -4y² + 12y-y + 3
-4y² + 12y-y + 3 = -4y * (y-3) - (y-3) = - (y-3) * (4y + 1)
Похожие вопросы
Предмет: Русский язык,
автор: Отечество
Предмет: Русский язык,
автор: Аноним
Предмет: Английский язык,
автор: Влад19971231
Предмет: Математика,
автор: Аноним